2014
DOI: 10.1186/1752-1947-8-425
|View full text |Cite
|
Sign up to set email alerts
|

Split-bolus versus triphasic multidetector-row computed tomography technique in the diagnosis of hepatic focal nodular hyperplasia: a case report

Abstract: IntroductionComputed tomography and magnetic resonance imaging are able to demonstrate and to diagnose hepatic focal nodular hyperplasia when a typical pattern of a well-circumscribed lesion with a central scar is present.Our aim is to propose the split-bolus multidetector-row computed tomography technique as an alternative to the conventional triphasic technique in the detection and characterization of focal nodular hyperplasia to reduce the radiation dose to the patient.To the best of our knowledge, this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The split‐bolus technique involves a dose‐efficient corticomedullary‐nephrographic‐excretory protocol in a single acquisition. Split‐bolus injection has been used in many studies in split‐bolus portal venous phase dual‐energy CT urography and split‐bolus vs tri‐phasic CT technique in the diagnosis of hepatic focal nodular hyperplasia . These studies showed that split‐bolus CT provides sufficient image quality with the potential to reduce radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The split‐bolus technique involves a dose‐efficient corticomedullary‐nephrographic‐excretory protocol in a single acquisition. Split‐bolus injection has been used in many studies in split‐bolus portal venous phase dual‐energy CT urography and split‐bolus vs tri‐phasic CT technique in the diagnosis of hepatic focal nodular hyperplasia . These studies showed that split‐bolus CT provides sufficient image quality with the potential to reduce radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Split-bolus injection has been used in many studies in split-bolus portal venous phase dual-energy CT urography and split-bolus vs tri-phasic CT technique in the diagnosis of hepatic focal nodular hyperplasia. 19,20 These studies showed that split-bolus CT provides sufficient image quality with the potential to reduce radiation exposure. This study aimed to explore the split-bolus protocol with spectral CT to reduce the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…MCDT is the procedure of choice in the identification of pancreatic malignancy 6 and other unusual tumors 7,8 . CT, in particular, is the method of choice in the assessment of normal pancreatic parenchyma and in the detection and staging of pancreatic adenocarcinoma 9,12,20 .…”
Section: Discussionmentioning
confidence: 99%
“…the most widely used method for the evaluation of pancreatic and non-pancreatic neoplastic diseases [6][7][8] . In this setting the knowledge of magnitude and consistency of the normal pancreatic enhancement and of optimal contrast differences between pancreas tumor and pancreas parenchyma is essential to ensure detection of lesions and accurate evaluation of peripancreatic vessels or lymph nodes 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a novel split‐bolus technique for multi‐detector computer tomography (MDCT) able to reduce the radiation dose and to ensure diagnostic accuracy in case of non‐thoracic neuroblastoma. It combines in a single pass the arterial and venous phases, allowing the detection of hypo‐ or hyper‐vascular lesions, together with lymph node involvement and related distant metastases . The split‐bolus 64‐detector row CT protocol is based on a single acquisition of the chest‐abdomen‐pelvis after intravenous injection of 2 ml/kg of contrast medium (Iopamiro 350 mg/ml; Bracco, Milan, Italy), split by an automatic power injector (Medrad Stellant, Indianola, PA) into two boluses.…”
mentioning
confidence: 99%